ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI UTANG LUAR NEGERI DI INDONESIA - Yogie Dahlly Saputro; Aris Soelistyo (Jurnal Ilmu Ekonomi JIE, 2017)
The purpose of the research is to describe how the influence of budget deficit, foreign exchange reserves, net exports and foreign debt of the previous year against foreign debt in Indonesia. Instrument analysis used is the method linear regression multiple with the methods ols with the data time series.With the methods testing the assumption classical and by test statistics like a test t and F test. The results of the analysis what have been done by researchers the results that on partial foreign exchange reserves (CDV) have had a positive impact and foreign debt of the previous year (ULNt-1) have had a positive impact and influential but not significant is namely the budget deficit (DA) and net exports (NX).Simultaneously of the four variable influential in significant impact on foreign debt.With the coefficients R2 of 99.91. Conclusions from research has been done that the variable that influence the foreign debt in Indonesia is foreign exchange reserves and foreign debt year earlier, and influential but not significant variables to external debt are the budget defisit and net exsport.Keywords: foreign debt , the budget deficit , foreign exchange reserves , net exports